Tuberculosis patients co-infected with Mycobacterium bovis and Mycobacterium tuberculosis in an urban area of Brazil. - SILVA, M. R. (2013)
In this cross-sectional study, mycobacteria specimens from 189 tuberculosis (TB) patients living in an urban area in Brazil were characterised from 2008-2010 using phenotypic and molecular speciation methods (pncA gene and oxyR pseudogene analysis). Of these samples, 174 isolates simultaneously grew on Löwenstein-Jensen (LJ) and Stonebrink (SB)-containing media and presented phenotypic and molecular profiles of Mycobacterium tuberculosis, whereas 12 had molecular profiles of M. tuberculosis based on the DNA analysis of formalin-fixed paraffin wax-embedded tissue samples (paraffin blocks). One patient produced two sputum isolates, the first of which simultaneously grew on LJ and SB media and presented phenotypic and molecular profiles of M. tuberculosis, and the second of which only grew on SB media and presented phenotypic profiles of Mycobacterium bovis. One patient provided a bronchial lavage isolate, which simultaneously grew on LJ and SB media and presented phenotypic and molecular profiles of M. tuberculosis, but had molecular profiles of M. bovis from paraffin block DNA analysis, and one sample had molecular profiles of M. tuberculosis and M. bovis identified from two distinct paraffin blocks. Moreover, we found a low prevalence (1.6%) of M. bovis among these isolates, which suggests that local health service procedures likely underestimate its real frequency and that it deserves more attention from public health officials.